EVALUASI PROSES PENYUSUNAN FORMULARIUM DAN PENERAPANNYA DI RSUD AM PARIKESIT TENGGARONG KUTAI KARTANEGARA - , selvy febrina putri ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background. Formulary is list of medicine approved of pharmacy and theurapetics committee in hospital and revision every timelimit specified. In RSUD AM Parikesit have a formulary but never do evaluation making process and implementation of formulary. Evaluation be required for assess making process and implementation because impact of formulary is quality of service in AM Parikesit general hospital. Research objective.To evaluate making process offormulary in AM Parikesit general hospital. Method. It is a case study research using qualitative and quantitative data. Qualitative data that is information about the making process, formulary quality, Delphi test before collection qualitative data. The function of Delphi test that is of expert valididation of the instrument. Quantitative data is information obedience doctor of writing prescription of formulary. Result. Percentaceof prescription from 13 poly inRSUD AM Parikesit, four of them achieve 100% prescription according formulary. Percentacesuitablility prescription according formulary for the degree of compliance doctor prescription according formulary. Conclusion.Obedience doctor of prescriprition according formulary is fine for some poly in RSUD AM Parikesit